A meta-review of systematic reviews and meta-analyses on outcomes of psychosocial interventions in heart failure - Nahlén Bose, Catarina (Frontiers in Psychiatry, 2023)
Chronic heart failure is a severe condition that influences not just the physical dimension but also the mental dimension in patients. Comorbidity of depression and anxiety are prevalent and the quality of life is reduced. Despite the psychological impact there are no recommendations in the guidelines for psychosocial interventions for people with heart failure. The aim of this meta-review is to synthesize results of systematic reviews and meta-analyses on the outcomes of psychosocial interventions in heart failure. Searches were conducted in PubMed, PsychInfo, Cinahl and the Cochrane Library. In total, seven articles were included after screening 259 studies for eligibility. The included reviews had, in total, 67 original studies included. The measured outcomes in the systematic reviews and meta-analyses were; depression, anxiety, quality of life, hospitalization, mortality, self-care and physical capacity. The results are inconsistent but show some short-term benefit of psychosocial interventions for reduced depression and anxiety and improved quality of life. However, the long-term effects were sparsely followed up. This meta-review appears to be the first in the field of the efficacy of psychosocial interventions in chronic heart failure. This meta-review identifies gaps in the current available evidence that need to be further explored, such as booster sessions, longer follow-up time for evaluation and incorporating clinical outcomes and measures of stress processes.